Spliceosome mutations: 1 plus 1 does not always equal 2 - Pellagatti, A; Boultwood, J (American Society of Hematology, 2020)
In this issue of Blood, Taylor et al show that 2 splicing factor mutations can coexist in the same cell in myeloid malignancy patients when their combination includes less common mutant alleles.